Medical information seeking behavior of urban patients in Zhejiang Province, China: a cross-sectional study - Liyun Liu (BMC, 2022)
Abstract Background Health information seeking behavior (HISB) is a prevalent research topic. However, little is known about sociodemographic factors of HISB in China. This study aimed to examine the HISB of urban patients in China and identify predictors of source preference, online information seeking, and the timing of online seeking. Methods Based on the Health Information National Trends Survey (HINTS), this study conducted a cross-sectional survey of 1653 participants in different types of hospitals in 3 cities of different income levels within Zhejiang Province, China. Binary logistic regression analysis and multinomial logistic regression analysis were used to identify predictors of source preference, online medical information seeking, and the timing of online seeking for urban patients. Results The offline was the primary source of medical information for 58.61% of adult urban patients, while 78.19% had ever sought medical information online. 36.81% of online medical information seekers sought information before the medical visit, 8.65% sought information after the visit, and 54.54% sought information before and after the visit. China's urban patients with higher education levels, higher income levels, young, active in internet use, and living in high-income cities were more likely to be active online medical information seekers (using the internet as the primary source) and online medical information seekers (having ever sought medical information online). Except for gender and age, most sociodemographic characteristics were not significantly associated with the timing of online medical information seeking. Conclusions Significant predictors of active online medical information seekers and online medical information seekers in China were almost the same. Regional economic development had a significant direct impact on medical information seekers. Most sociodemographic characteristics were not significantly associated with the timing of online medical information seeking. The findings of this study imply that China's health information technology industry has Chinese characteristics.